2018
DOI: 10.1007/s10048-018-0560-x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Ehlers–Danlos syndrome is associated with leukoencephalopathy

Abstract: Here, we report brain white matter alterations in individuals clinically and genetically diagnosed with periodontal Ehlers–Danlos syndrome, a rare disease characterized by premature loss of teeth and connective tissue abnormalities. Eight individuals of two families clinically diagnosed with periodontal Ehlers–Danlos syndrome were included in the present study and underwent general physical, dental, and neurological examination. Whole exome sequencing was performed, and all patients included in the study under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…A total of 16 different C1R variants from two publications (4, 16) were investigated, including one previously unpublished variant c.277G>T (p.G93C) identified in a family from Australia (Table 2). All variants are predicted to be pathogenic, and none of the variants has been found in registered control populations [ExAc database http://exac.broadinstitute.org/ (17), last accessed September 26, 2019].…”
Section: Methodsmentioning
confidence: 99%
“…A total of 16 different C1R variants from two publications (4, 16) were investigated, including one previously unpublished variant c.277G>T (p.G93C) identified in a family from Australia (Table 2). All variants are predicted to be pathogenic, and none of the variants has been found in registered control populations [ExAc database http://exac.broadinstitute.org/ (17), last accessed September 26, 2019].…”
Section: Methodsmentioning
confidence: 99%
“…Heterozygous missense variants in C1R are a known cause of periodontal Ehlers–Danlos syndrome (pEDS) (Kapferer‐Seebacher et al., ) and this is potentially of interest for two reasons. One is that a recent MRI study of seven adults with pEDS and C1R mutations reported that they all had leukoencephalopathy, which appeared to be progressive with age and which was suggestive of underlying small vessel disease (Kapferer‐Seebacher et al., ). The second is that pEDS is characterised by periodontitis and it has been proposed that periodontal disease is a risk factor for LOAD, perhaps mediated either by direct infection of the brain with the key periodontal pathogen Porphyromonas gingivalis or through secondary effects of chronic inflammation, perhaps involving activation of the complement cascade (Singhrao, Harding, Poole, Kesavalu, & Crean, ).…”
Section: Resultsmentioning
confidence: 99%
“…Heterozygous missense variants in C1R are a known cause of periodontal Ehlers-Danlos syndrome (pEDS) (Kapferer-Seebacher et al, 2016) and this is potentially of interest for two reasons. One is that a recent MRI study of seven adults with pEDS and C1R mutations reported that they all had leukoencephalopathy, which appeared to be progressive with age and which was suggestive of underlying small vessel disease (Kapferer-Seebacher et al, 2019). The second is that pEDS is characterised by periodontitis and it has been proposed that periodontal disease is a risk factor for LOAD, perhaps mediated either by direct infection of brain with the key periodontal pathogen Porphyromonas gingivalis or through secondary effects of chronic inflammation, perhaps involving activation of the complement cascade (Singhrao et al, 2015).…”
Section: Resultsmentioning
confidence: 99%